Knowledge, attitude, and perception regarding COVID-19-related prevention practice among residents in Vietnam: a cross-sectional study - Le, Thoa; Le, Trang T. B.; Van Truong, Le; Luu, Mai Ngoc; Tran Minh Duc, Nguyen; Makram, Abdelrahman M.; Van Dat, Truong; Huy, Nguyen Tien (Frontiers in Public Health, 2023)
Background: Vietnam was one of the countries pursuing the goal of "Zero - COVID" and had effectively achieved it in the first three waves of the pandemic. However, the spread of the Delta variant was outbreak first in Vietnam in late April 2021, in which Ho Chi Minh City was the worst affected. This study surveyed the public's knowledge, attitude, perception and practice (KAPP) toward COVID-19 during the rapid rise course of the outbreak at Ho Chi Minh City. Method: This cross-sectional survey was conducted from September 30th to November 16th, 2021, involving 963 residents across the city. We asked residents a series of 21 questions. Results: The residents' KAPP scores were 68.67%±17.16, 77.33%±18.71, 74.7%±26.25, and 72.31%±31, respectively. The KAP scores of the medical staff were higher than the non-medical group. Our study showed the positive, medium – strong Pearson correlations between knowledge and practice (r= 0.337), attitude and practice (r=0.405), perception and practice (r=0.671) (p<0.05). We found 16 rules to estimate the conditional probabilities among KAPP score via the association rule mining method. Mainly, 94% confident probability of participants had Knowledge=Good, Attitude=Good, Perception=Good, they would have Practice=Good as well (in rule 9 with a support of 17.6%). In opposition to around 86% to 90% of the times, participants had levels of Perception=Fair, Practice=Poor given with either Attitude=Fair or Knowledge=Fair (according to rules 1, 2, and rules 15, 16 with a support of 7-8%). Conclusion: Besides government’s directives and policies, citizen’s knowledge, attitude, perception and practice are considered one of the critical preventive measures during the COVID-19 pandemic. The results affirmed the good internal relationship among K, A, P, P scores created a hierarchy of healthcare educational goals and health behavior among residents.